Join IDNLearn.com and start getting the answers you've been searching for. Ask your questions and receive comprehensive, trustworthy responses from our dedicated team of experts.
Sagot :
Answer:
-1/2
Step-by-step explanation:
1/3 = 2/6 (find common denominator)
-(2/6) - (1/6) = -3/6 = -1/2
[tex]\large\underline{\sf{Solution-}}[/tex]
[tex] \sf - \frac{1}{3} - \frac{1}{6} \\ [/tex]
[tex]\textsf{Take the LCM of 3and 6 is 6.}\\[/tex]
[tex] \sf = \frac{ - 2 - 1}{ 6} \\ [/tex]
[tex] = \frac{ - 3}{6} \\ [/tex]
[tex] \sf = - \frac{1}{2} \\ [/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Find clear and concise answers at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.